A study on mutation testing of object oriented programs - Poojitha, T. N. S.; Pushpanjali, K. V. L.; Goutham, D.; Yashwanth, K. V.; Prasad, Srinivas (International Journal of Engineering and Technology, 2017)
Mutation testing is a modern approach which gives more appropriate results. In comparison to traditional approaches, it gives high quality output. Previously it is not used mostly because of its high cost factor. This is because mutation testing deals with white box testing. White Box testing checks every module of the software in detail. If we use this it takes a lot of time and money. Recent approaches which came in mutation testing made it easy to implement for any software. Mutation take a look ating could be a fault based mostly testing technique within which mutants area unit generated within the program and apply totally different test cases on the mutants. Some mutants are killed and some are alive. On the bottom of killed and alive mutants, mutant score is calculated. Based on the mutants which are alive the test cases can be improvised there by the quality of the source code is increased. we propose a tool which gives more effective output of testing. We propose a tool which takes the outputs of various static tools available and combines it with the outputs of dynamic tools available. Our proposed tool includes outputs of available tools like Jester, Mujava, PMD to effectively detect the vulnerabilities and produce high quality software as output.